Sistem Temu Balik Citra Berbasis Isi Citra Menggunakan Fitur Warna Dan Jarak Histogram - Chyan, Phie; Sumarta, Sean Coonery (Fakultas Teknologi Informasi, Universitas Atma Jaya Makassar, 2013)
Today, Collection of image data on the Internet is growing rapidly in terms of quantity. In parallel with this a method of content -based image retrieval (Content -based image retrieval) is needed in the process of identifying and accessing visual information. Content -based image retrieval basically simulates the human perception of an image so that an error occurred in the text -based retrieval methods can be overcome. In this research, the image retrieval system is implemented with the extraction of low level features of the image. Low-level information used in this study is the color information contained in the image. Composition of color pixels in an image can be represented in a color histogram. The degree of similarity between the image color is determined based on the distance between the histogram using Laplace distance and Euclidean distance. The smaller the distance between the histogram, the higher the percentage of similarity of an image. Results of image retrieval through the database will be displayed according to the query by example method performed by a user, based on the sequence of images that have a higher percentage of similarity.